Les Risques catastrophiques - Crescenzo-d’Auriac, Marie-Béatrix (Assurances, 1989)
Following is the conclusion of the book entitled Les Risques catastrophiques (Catastrophic Risks) published in L’Argus in 1988. Catastrophic events, be they of a natural, political or technological nature, have long been considered uninsurable, with the only funds or basic coverage provided by the government. In a direct and engaging style, the author, Mrs. Marie-Béatrix Crescenzo-d’Auriac, suggests a harmonious collaboration between the government and private insurers in the area of catastrophic risk insurance.